Cortical Neuroplasticity after Focused Peripheral Radiation: Longitudinal Effects of Gamma Knife Radiosurgery for Classic Trigeminal Neuralgia - Peter Shih-Ping Hung; Alborz Noorani; Jia Y. Zhang; Mojgan Hodaie (Taylor & Francis Group, 2019)
Introduction/Aim: Classic trigeminal neuralgia (TN) is a severe chronic neuropathic facial pain disorder that, despite frequently being linked to microstructural changes within trigeminal nerve root entry zone, has well-documented cortical thickness alterations. These alterations occur in brain regions important for sensory and affective processing of pain and can be reversed by successful surgical interventions. As existing studies are limited to pre-treatment and early post-treatment time-points, longitudinal effects of non-invasive surgical interventions like Gamma Knife radiosurgery (GKRS) on the cortical thickness in TN patients remains unclear and are thus the focus of our current structural magnetic resonance imaging study. Methods: 18 patients treated with GKRS as their first surgery for TN underwent pre-treatment, 6 months post-treatment, and 12 months post-treatment 3-Tesla imaging. FreeSurfer 6.0 facilitated extraction of cortical thickness from 68 Desikan-Killiany brain regions. 7 false discovery rate-corrected paired Student's t-tests were then conducted per region to contrast cortical thicknesses between hemispheres and across time-points. Results: GKRS resulted in longitudinal, bilateral increases in cortical thickness within fusiform gyrus, precentral gyrus, paracentral lobule, and inferior temporal gyrus. GKRS also resulted in transient increases in cortical thickness in contralateral banks of superior temporal sulcus, ipsilateral superior frontal gyrus, and contralateral caudal middle frontal gyrus. Discussion/Conclusions: For the first time, we demonstrated that radiosurgery for TN leads to longitudinal and transient cortical thickness changes within default mode, executive control, limbic, somatomotor, and visual brain networks. Further studies are needed to ascertain the functional role these structural changes may play in GKRS' therapeutic effect.